REGIONAL TRADE AGREEMENTS VS. WTO: LEGAL OVERLAPS AND CONFLICTS - Khumoyunmirzo Eshboev (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract:The past three decades have seen an unprecedented flourishing and deepening of Regional Trade Agreements (RTAs). The World Trade Organization (WTO) recognizes RTAs as exceptions to Most-Favoured-Nation (MFN) treatment under GATT Article XXIV, GATS Article V and the 1979 Enabling Clause. Yet practical and doctrinal tensions have grown as RTAs now often include “WTO-plus” and “WTO-extra” obligations, complex rules of origin (RoO), separate dispute settlement systems, and are sometimes unnotified or left under review by WTO bodies. This article highlights six main problem areas where RTAs overlap with and sometimes challenge the WTO legal framework: (1) textual vagueness and interpretation of WTO exceptions (Article XXIV/GATS V/Enabling Clause); (2) the empirical rise of preferential trade and erosion of MFN; (3) rules of origin and their protectionist or distributive effects; (4) notification and transparency gaps that weaken WTO oversight; (5) parallel dispute settlement mechanisms and resulting jurisprudential fragmentation; and (6) WTO-plus / TRIPS-plus content with implications for development. Each section combines doctrinal analysis, official data, WTO jurisprudence, and recent state practice (including Uzbekistan’s regional positioning) to propose clear, legally-feasible reforms aimed at aligning regional dynamism with multilateral coherence.